2022
DOI: 10.3389/fimmu.2022.818569
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Donor-Specific Anti-HLA Antibodies Associate With Immune Activation Independent of Kidney Transplant Histopathological Findings

Abstract: Despite the critical role of cytokines in allograft rejection, the relation of peripheral blood cytokine profiles to clinical kidney transplant rejection has not been fully elucidated. We assessed 28 cytokines through multiplex assay in 293 blood samples from kidney transplant recipients at time of graft dysfunction. Unsupervised hierarchical clustering identified a subset of patients with increased pro-inflammatory cytokine levels. This patient subset was hallmarked by a high prevalence (75%) of donor-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 71 publications
7
15
0
Order By: Relevance
“…Furthermore, our cell-to-cell communications analysis suggested that CXCL10 overexpression by FcγRIII+ monocytes may recruit CXCR3+ T cells and activate ACKR1+ endothelial cells composing the peritubular capillaries. This aligns with our previous finding that the FcγRIII engagement of purified nonclassical monocytes co-cultured with primary endothelial glomerular cells induces CXCL10 secretion 22 . Finally, increased expression of CXCL10 is not only observed in the biopsies at time of kidney allograft rejection but also in urine, serving as suitable biomarker of rejection [66][67][68] , and in peripheral blood 22 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, our cell-to-cell communications analysis suggested that CXCL10 overexpression by FcγRIII+ monocytes may recruit CXCR3+ T cells and activate ACKR1+ endothelial cells composing the peritubular capillaries. This aligns with our previous finding that the FcγRIII engagement of purified nonclassical monocytes co-cultured with primary endothelial glomerular cells induces CXCL10 secretion 22 . Finally, increased expression of CXCL10 is not only observed in the biopsies at time of kidney allograft rejection but also in urine, serving as suitable biomarker of rejection [66][67][68] , and in peripheral blood 22 .…”
Section: Discussionsupporting
confidence: 92%
“…This aligns with our previous finding that the FcγRIII engagement of purified nonclassical monocytes co-cultured with primary endothelial glomerular cells induces CXCL10 secretion 22 . Finally, increased expression of CXCL10 is not only observed in the biopsies at time of kidney allograft rejection but also in urine, serving as suitable biomarker of rejection [66][67][68] , and in peripheral blood 22 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Excellent reviews detailing the current knowledge on non-HLA antibodies in transplantation have already been published ( 60 , 63 66 ). Here, to investigate the distribution of non-HLA antigen expression in the kidneys, we performed single-cell analysis of previously published human single-cell data ( Figures 2A, B ) from two ABMR biopsies and four healthy references corresponding to transplant surveillance biopsies as previously described ( 67 ). We focused on the main studied antibodies and discuss new large-scale studies in the field of non-HLA antibodies.…”
Section: Non-hla Antibody-dependent MVImentioning
confidence: 99%
“…The associated raw counts or matrices were downloaded from the Gene Expression Omnibus (GEO; GSE145927, ) and Kidney Precision Medicine Project ( ). The analysis was performed as previously published ( 67 , 68 ). (A) UMAP dimensionality reduction for the different cell type clusters identified by scRNA-seq analysis.…”
Section: Non-hla Antibody-dependent MVImentioning
confidence: 99%